2012
DOI: 10.4209/aaqr.2011.12.0228
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Particulate-Phase High Molecular Weight Mono-Carbonyls (C# > 5) and Dicarbonyls in Urban Atmosphere of Xi’an, China

Abstract: An analytical method to quantify particulate-phase high molecular weight mono-carbonyls (C# > 5) and di-carbonyls has been developed by adopting 2,4-dinitrophenylhydrazine (DNPH) derivatization followed by high performance liquid chromatography/ultra-violet (HPLC/UV) detection. Satisfactory reproducibility and precision of the measurements were achieved. This method was applied to measure the carbonyls in PM 2.5 collected on quartz-fiber filters, sampled in Xi'an, China, from 2008 to 2009. Nonanaldehyde was th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2014
2014
2017
2017

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 15 publications
(18 citation statements)
references
References 49 publications
0
18
0
Order By: Relevance
“…Even if there is only a small fraction of glyoxal partitioning onto particles, it can still affect the global secondary organic aerosol (SOA) budget significantly. Dai et al (2012) reported an average PM 2.5 glyoxal concentration of 0.7 AE 0.4 ng m À3 during same sampling period at Xi'an, with the highest concentration of 1.1 ng m À3 in winter. As shown in Table 1, there was a strong correlation between levoglucosan and glyoxal (R ¼ 0.80) concentrations.…”
Section: Correlation Of Levoglucosan With Other Compoundsmentioning
confidence: 87%
See 2 more Smart Citations
“…Even if there is only a small fraction of glyoxal partitioning onto particles, it can still affect the global secondary organic aerosol (SOA) budget significantly. Dai et al (2012) reported an average PM 2.5 glyoxal concentration of 0.7 AE 0.4 ng m À3 during same sampling period at Xi'an, with the highest concentration of 1.1 ng m À3 in winter. As shown in Table 1, there was a strong correlation between levoglucosan and glyoxal (R ¼ 0.80) concentrations.…”
Section: Correlation Of Levoglucosan With Other Compoundsmentioning
confidence: 87%
“…Twenty-four-hour PM 2.5 sampling was performed every sixth day (from 10:00 a.m. to 10:00 a.m. the next day, local standard time [LST]) using TE-6070MFC hi-vol PM 2.5 air sampler (Tisch, Cleveland, OH, USA) at a flow rate of 1.0 m 3 min À1 from 5 July 2008 to 27 June 2009 (Dai et al, 2012). Samples were collected on 203 mm  254 mm quartz-fiber filters (Whatman QM/A, Clifton, NJ, USA), which were prefired at 800 C for 3 hr before sampling in order to remove contaminants.…”
Section: Field Samplingmentioning
confidence: 99%
See 1 more Smart Citation
“…For carbonyl compounds there have been numerous publications regarding detection and quantification using either dinitrophenyl hydrazine, methoxyamine, or O -(2,3,4,5,6-pentalfluorobenzyl)hydroxyamine (PFBHA) (Cirera-Domenech et al, 2013; Dai et al, 2012; Forester and Wells, 2009; Gomez Alvarez et al, 2012; Halket and Zaikin, 2005; Hudson et al, 2011; Kowalewski and Gierczak, 2011; Lopez-Aparicio and Hak, 2013; Rossignol et al, 2012). Current methodologies have included derivatization techniques to transform these compounds for gas chromatography/mass spectrometry (GC/MS) detection.…”
Section: Introductionmentioning
confidence: 99%
“…In the high molecular weight carbonyls (C 6 -C 12 ), nonanaldehyde was the most abundant species with a mean value of 0.95 µg m -3 . Similarly, Dai et al (2012) reported that nonanaldehyde was the most abundant compound among high molecular weight mono-carbonyls (C# > 5) and di-carbonyls in urban atmosphere of Xi'an, China. The average concentrations of the other compounds were less than 1.0 µg m -3 (Table 2), accounting for < 10% of the ∑ 18carb .…”
Section: Concentrations Of Carbonyls In the Librarymentioning
confidence: 99%